Предмет: Алгебра,
автор: jalaur
Рациональное уравнение.
Приложения:
Ответы
Автор ответа:
1
домножаем на x(x-3)
3(x-3)-12x=x(x-3)
3x-9-12x=x^2-3x
-x^2+3x-9-12x+3x=0
-x^2-6x-9=0
D=36-4*(-1)*(-9)=0
x=-6/2=-3
3(x-3)-12x=x(x-3)
3x-9-12x=x^2-3x
-x^2+3x-9-12x+3x=0
-x^2-6x-9=0
D=36-4*(-1)*(-9)=0
x=-6/2=-3
Похожие вопросы
Предмет: Русский язык,
автор: modias
Предмет: Українська мова,
автор: Личность18
Предмет: Русский язык,
автор: kabilet777
Предмет: Математика,
автор: kashlikov49
Предмет: Химия,
автор: guseynov2019